THE RELATIONSHIP BETWEEN SERVICE QUALITY, PATIENT SATISFACTION, BEHAVIORAL INTENTIONS AND PRICES IN OUTPATIENT HEALTHCARE IN THE HOSPITAL INDUSTRY - Asya Zahratur Rahma; Tantri Yanuar Rahmat Syah (SEAN Institute, 2023)
This study aims to explore the relationship between service quality, patient satisfaction, and behavioral intentions as a mediation moderated by price. Referring to the results of previous studies and empirical theories related to service quality and satisfaction, this research was designed to collect data using a survey method by distributing questionnaires both directly / offline and online questionnaires. Respondents in this study were selected using the purposive sampling method. This research is a quantitative research usingquantitative research usesod. The findings in this study are the first positive influence of Service Quality, Satisfaction and Price. Secoprice is a mediating role ice on satisfaction and behavioral intentions. The managerial implication of this study is that hospitals need to improve the quality of service to patients so that patients remain loyal and do not switch to other hospitals, as optimally as possible to provide quality services to patients until they are in the zone of tolerance for the highest behavioral intention, it is necessary to minimize the occurrence of service problems for patients, making health workers more skilled and professional in providing quality services, safe and comfortable facilities, as well as more affordable hospital prices.